Update on MR imaging of spondyloarthritis. part two: spine MR imaging - Vande Berg, B C; Omoumi, P; Larbi, A; Lecouvet, F; Malghem, J (JBR-BTR (Bruxelles), 2014)
MRI of the sacro-iliac joints has become a key-imaging technique for the detection of early non-radiographic axial SpA and has been shown to contribute to optimized clinical decision-making (1, 2, 3). The current paper aims at summarizing the contribution of Spine MRI in patients with SpA, the optimized MRI protocols and findings at imaging. Pitfalls and differential diagnosis for spine changes will be addressed. Vertebral fractures and dural ectasia occasionally observed in long-standing SpA patients will be mentioned.